Epigenetic and genetic variations at the TNNT1 gene locus are associated with HDL-C levels and coronary artery disease. (March 2016) - Guay, Simon-Pierre; Légaré, Cécilia; Brisson, Diane; Mathieu, Patrick; Bossé, Yohan; Gaudet, Daniel; Bouchard, Luigi
Aim: To assess whether epigenetic and genetic variations at the TNNT1 gene locus are associated with high-density lipoprotein cholesterol (HDL-C) and coronary artery disease (CAD).Patients, materials & methods: TNNT1 DNA methylation and c.-20G>A polymorphism were genotyped in subjects with and without familial hypercholesterolemia (FH).Results: Lower TNNT1 DNA methylation levels were independently associated with lower HDL-C levels and with the TNNT1 c.-20G>A polymorphism. In FH men, carriers of the TNNT1 c.-20G>A polymorphism had lower HDL-C levels and an increased risk of CAD compared with noncarriers. In non-FH men, a higher TNNT1 DNA methylation level was associated with CAD.Conclusion: These results suggest that TNNT1 genetic and epigenetic variations are associated with HDL-C levels and CAD.